PENGARUH KOMPETENSI PEDAGOGIK GURU DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SETINGKAT SEKOLAH MENENGAH PERTAMA - Didit Darmawan; Nadzirah Shava Salsabila Salam Al Madury; Mas Adelia Najibah (STKIP Subang, 2026)
A frequently observed phenomenon shows that student learning outcomes vary significantly depending on their level of motivation and the pedagogical competence of their teachers, with highly motivated students who are guided by competent teachers tending to achieve the best academic results. The purpose of this study is to ascertain how junior high school students' learning outcomes are impacted by pedagogical competence and learning motivation. The Systematic Literature Review (SLR) approach is used in this study. The study's findings show that teachers' high levels of learning motivation and pedagogical competence can be used as a guide to enhance student learning outcomes; consequently, pupils who have these qualities are more likely to achieve the best possible learning outcomes. To maximize learning outcomes and accomplish the desired educational goals, it is crucial to make efforts to enhance teachers' pedagogical competency and students' enthusiasm to learn using a variety of creative learning tactics and approaches.